The challenges of globalization for smes in Moldova - Cretoiu, Raluca Ionela (Annals of Spiru Haret University. Economic Series, 2016)
Globalisation offers humankind a new vision both on international economic relations and on international affairs, which have gained momentum and turned over time. The international economic relations seen from the perspective of the global economy’s globalization have expanded and acquired new meanings, the evolution towards such a global economy involving intra-regional relationships and partnerships development that have arisen between multinational companies. On the ground of these transformations, SMEs face a number of challenges due to the evolution of economic, social and cultural conditions of globalization. This paper investigates, using a field survey type research, the ways in which globalization affects the activity of SMEs from the perspective of the managers in Moldova perspective.